Unveiling genetic diversity and forensic utility of SureID® human DNA identification kits: a comprehensive analysis of 44 autosomal STR loci in English and Irish populations - Sasitaran Iyavoo; Jessica Perry; Simon Knights; Michalis Mavrommatis; Tatiana Petrova; Abigail Bevan; Stephen Cummings; Sharlize Pedroza Matute; Danlu Song; Thomas Haizel (Taylor & Francis Group, 2023)
Background: Human identification and kinship testing in forensic science rely on Short Tandem Repeat (STR) multiplex kits, typically containing loci recommended by standard sets. However, complementary kits with additional STR loci can be valuable in complex cases. Allele frequency databases specific to the population are essential for accurate forensic analysis. Aim: This study aimed to generate allele frequencies and population genetic data for 44 autosomal STR loci from SureID® PanGlobal and 27comp kits in English and Irish populations for forensic casework, human identification, and kinship testing. Subjects and methods: Buccal swab samples from 645 White Caucasians (365 English, 280 Irish) were collected. DNA was extracted and amplified using the mentioned kits. Quality control, statistical analysis, and genetic distance calculations were performed. Results: Both kits demonstrated robustness with no significant deviations from Hardy-Weinberg Equilibrium (HWE). Variant alleles and minor discordances between kits were observed. Syntenic STR pairs were identified but showed no significant linkage. A close genetic relationship was found between English and Irish populations, allowing for combined databases. Conclusions: The SureID® PanGlobal and 27comp kits showed high discriminatory power and reliability in the English and Irish populations. Care is needed when handling variant alleles, discordances, and syntenic loci. Combining data from both populations is feasible for a comprehensive database. Further studies are required to explore their effectiveness in diverse populations.